ANALISIS POLA PENYAJIAN DESKRIPSI PADA NOVEL â€œSURAT KECIL UNTUK TUHANâ€ KARYA AGNES DAVONAR SEBAGAI ALTERNATIF PEMILIHAN BAHAN AJAR KELAS XII - Danengsih; Nurhayatin, Titin; Rustandi, Adi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
The author analyzed the pattern of presenting descriptions in the novel "Surat Kecil untukTuhan" by Agnes Davonar. The purpose of this study is to describe the pattern of presentation of static descriptions, patterns of presentation of moving descriptions, patterns of presentation of outline descriptions, and describing the results of studies on the pattern of presentation of descriptions in the novel "Surat Kecil untuk Tuhan" by Agnes Davonar can be used as a teaching material Indonesian for class XII learners based on the 2013 Curriculum. The research method use is descriptive qualitative method. Therefore, the data obtained in this study are not in the form of numbers, but in the form of descriptions or narratives. The results showed that in the novel "Surat Kecil untuk Tuhan" by Agnes Davonar, there were 9 patterns of description presentation including, 5 static patterns, 3 moving patterns, and 1 skeleton pattern. The results also showed that based on the results of the analysis of the suitability of study materials with the demands of the curriculum, the novel â€œSurat Kecil untuk Tuhanâ€ can the results of the study have been validated by experts and declared worthy of use as teaching materials.